More evidence of the health risks of normal weight obesity: the association with systemic inflammation - Liu-Galvin, Rachel; Orlando, Frank A.; Saguil, Aaron A.; Jo, Ara; Smith, Kristy B.; Miller, Andrew M.; Nelson, Danielle S.; Sanders, Elizabeth C.; Mainous, Arch G. (Frontiers in Medicine, 2025)
BackgroundNormal weight obesity (NWO) – a normal body mass index (BMI) with high body fat percentage (BF%) – has been linked to increased cardiometabolic risk. This study examined whether NWO is associated with systemic inflammation.MethodsUsing 2017–2018 NHANES data, we categorized adult respondents aged 18–59 with BMI ≥ 18.5 into four groups:Reference: Normal BMI (18.5–24.9) with normal BF% (< 25% males/ < 35% females)NWO: Normal BMI with high BF% (≥ 25% males/ ≥ 35% females)Elevated BMI (≥ 25) with normal BF%Elevated BMI with high BF%Survey-weighted logistic regression examined associations with elevated hs-CRP (> 3.0 mg/L), adjusting for age and race/ethnicity. Sex-stratified analyses were also conducted.ResultsInflammation prevalence was 32.7% overall, highest among individuals with elevated BMI and high BF% (43.6%). Compared to the reference group, individuals with NWO had over 3-fold increased odds of inflammation [AOR 3.34 (95% CI: 1.83, 6.08)]; individuals with elevated BMI and high BF% had over 6-fold increased odds [AOR 6.19 (95% CI: 3.66, 10.50)]. Elevated BMI with normal BF% was not significantly associated with inflammation.In sex-stratified analyses, NWO was associated with inflammation in both males [AOR 4.44 (95% CI: 1.62, 12.10)] and females [AOR 2.78 (95% CI: 1.40, 5.52)]. Elevated BMI and high BF% was also associated with inflammation in both sexes.ConclusionIn this cross-sectional study, NWO was associated with inflammation, although causality cannot be inferred. Reliance on BMI alone may misclassify cardiometabolic risk therefore BF% should be considered in clinical assessments.